3D nano- and micro-patterning of biomaterials for controlled drug delivery. (January 2017) - Curry, Eli J; Henoun, Atta D; Miller, Albert N; Nguyen, Thanh D
Recently, there has been an emerging interest in controlling 3D structures and designing novel 3D shapes for drug carriers at nano- and micro-scales. Certain 3D shapes and structures of drug particles enable transportation of the drugs to desired areas of the body, allow drugs to target specific cells and tissues, and influence release kinetics. Advanced nano- and micro-manufacturing methods including 3D printing, photolithography-based processes, microfluidics and DNA origami have been developed to generate defined 3D shapes and structures for drug carriers. This paper reviews the importance of 3D structures and shapes on controlled drug delivery, and the current state-of-the-art technologies that allow the creation of novel 3D drug carriers at nano- and micro-scales.